2013
DOI: 10.1002/pmic.201200317
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of human pericardial fluid

Abstract: Pericardial fluid (PF) is considered as a biochemical window of heart. To date, there have been limited attempts to perform an in-depth analysis of the PF proteome. In this study, an SDS-PAGE-LC-MS/MS platform was utilized to explore depleted PF, which showed great coverage of low-abundant proteins. In total, 1007 nonredundant proteins were identified with at least two peptides. This is the first comprehensive analysis of human PF proteome and provides a foundation for further application of PF in cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…Samples were centrifuged at 10,000 rpm for 10 min to remove cell debris. Agilent’s multiple affinity removal system (MARS-14), generally used for depletion of albumin, IgG, transferrin, heptoglobin, IgM, IgA, fibrinogen, alpha antitrypsin, apolipoprotein A1, alpha1 acid glycoprotein, alpha2 macroglobin, transthyretin, complement C3 and apolipoproteins was used to deplete the abundant proteins from CSF samples [31]. Briefly, MARS-14 cartridge was conditioned using 4 ml of Buffer-A (50 g, 1 min).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were centrifuged at 10,000 rpm for 10 min to remove cell debris. Agilent’s multiple affinity removal system (MARS-14), generally used for depletion of albumin, IgG, transferrin, heptoglobin, IgM, IgA, fibrinogen, alpha antitrypsin, apolipoprotein A1, alpha1 acid glycoprotein, alpha2 macroglobin, transthyretin, complement C3 and apolipoproteins was used to deplete the abundant proteins from CSF samples [31]. Briefly, MARS-14 cartridge was conditioned using 4 ml of Buffer-A (50 g, 1 min).…”
Section: Methodsmentioning
confidence: 99%
“…Pericardial fluid may be used as a biomarker for inferring pathological alteration to the heart (11), and its accumulation can be attributed to an underlying systemic or local inflammatory process (12). Therefore, it is important to identify the association between the progression of CHF and the inflammatory response in the pericardial fluid in order to find a future treatment strategy and prognosis of HF.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma itself displays a range higher than 10 10 -fold [4]. Third, data integration will be difficult since we have available only one study published so far, reporting the first in-depth proteomic characterization of PF [5]. In that study the first 1000 PF proteins were identified by removing the 14 most abundant proteins (using Agilent's Multiple Affinity Removal System, MARS) and by following a SDS-PAGE-LC-MS/MS approach.…”
Section: Introductionmentioning
confidence: 99%